âBTRAFFWATCHâ SOLUSI UNTUK PIHAK KEPOLISIAN DALAM MELAKUKAN PENGAWASAN DAN PENDETEKSIAN PELANGGARAN PADA LAMPU LALU LINTAS - Basoeki, Hario Baskoro; Amirudin, Johan Kharisma; Pratama, Nino Prasetyo Hamal; Supriyanto, Agus; Nuzula, Fani Firdausi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Lack of awareness of adherence to traffic regulations is often the trigger for the traffic violation, the traffic lights are common violations of deliberate markings by road users. This study created a surveillance system that can detect violations that occur in traffic. Detected violations in this case is the violation that occurred at the traffic lights. Violations are divided into two, namely the violation of a red light and when the green light turns on. Violation that occurs when the red light and green light was able to be detected. Having conducted an experiment using 10 videos describing the condition of the red light and 10 videos depicting green light conditions, the system can achieve the accuracy of 85.83 % for the detection of objects that violate the red light when turns on and 96.67 % for the violation at the time of the lamp green turns on.